Chapter Self-Telling to Orientate Oneself - Rossi, Bruno (Studies on Adult Learning and Education, 2018)
The guidance experience, pedagogically considered, is above all the process of identification, recognition and consolidation of individual resources of which the person is the bearer (attitudes, capabilities, inclinations, expectations, desires, projects), is the conquest of one's own identity, the research of constituent elements of personality, the awareness of 'being-different-from-everyone-else'. Within this theoretical assumption, the narration is a suitable placement as estimable and relevant device for self-guidance and transformation of the self. In the guidance actions the use of narrative, reflective and autobiographical paradigms can represent an effective aid in the direction of the redefinition of identity, empowerment and self-empowerment. Narration is the search for the truth about the self, or even more the process of re-thinking and re-design the self. It means to discover and achieve a deep knowledge about the self, to reconstruct one's own life plan, is to de-form to re-emerge, to re-form it. In a broad sense, it is in some way to 'die' to be reborn regenerated